(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: Imipenem resistant gram-negative bacteria (GNB) have become a major public health concern worldwide, including Bangladesh. The present study was performed to determine the frequency of imipenem resistant gram-negative bacteria (GNB), their antimicrobial susceptibility pattern. Materials and Methods: A total of three hundred and fifty clinical samples were collected from Bangladesh Institute of Health Sciences hospital (BIHS), Dhaka, Bangladesh, over a period of 12 months. Among 350 samples, 171 (48.86%) were from indoor patients, and 179 (51.14%) were from outdoor patients. The pathogens were isolated and identified by conventional methods and were screened for antibiotic susceptibility using the Kirby–Bauer disc diffusion method, including imipenem discs. A Chi-square test was employed for statistical analysis. Results and Discussion: Out of 350 clinical isolates, 246 showed resistance to imipenem (70.28%). Almost all of the imipenem resistant gram-negative bacteria showed the highest resistant pattern to cefepime (88.57%), amoxicillin (88.29%), cephalosporin (88.14%), cefoxitin (86%), tetracycline (84.42%), and the majority were resistant to levofloxacin (70.85%), doxycycline (70.57%), netilmicin (59.71%). But cotrimoxazole (13.42%) and tigecycline (11.43%) showed a lower resistance pattern. Statistical analysis exhibited imipenem resistant gram-negative isolates most commonly found in pus and urine samples, while Klebsiella spp (30.49%), Pseudomonas spp (26.83%) and E. coli (23.17%) were the most predominant pathogens. Conclusion: This is a retrospective study which study indicates a noteworthy rate of clinical isolates were imipenem resistant gram-negative bacteria in a well-defined tertiary care hospital, and most of these bacteria were also multidrug-resistant. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 145-150